Expression of Case by the Verb in Tagalog - Blake, Frank R. (The Archive; Vol 3 No 1–2 (1972): Vol. 3 (New Series), Nos. 1–2 (1972), 2024)
Excerpt In Philippine languages, on the other hand, this case-indicaing function of the verb is developed to a high degree. The active, as in Indo-European and Semitic, denotes the case of the agent, but the passive expresses not only the accusative, but also the dative, instrumental, locative, and ablative; the noun whose case is to be indicated being made the subject of the passive verb. In Tagalog, which may be taken as a type of these languages, a verb may have an active and three so-called passive forms, which are known respectively, according to the particles with which they are formed, as the in , i , and an passives.